microRNA 21-mediated suppression of sprouty1 by Pokemon affects liver cancer cell growth and proliferation - Jin, Xiu-Li; Sun, Qin-Sheng; Liu, Feng; Yang, Hong-Wei; Liu, Min; Liu, Hong-Xia; Xu, Wei; Jiang, Yu-Yang (Journal of cellular biochemistry, 2013)
Transcriptional repressor Pokemon is a critical factor in embryogenesis, development, cell proliferation, differentiation, and oncogenesis, thus behaving as an oncogene. Oncomine database suggests a potential correlation between the expressions of Pokemon and Sprouty1. This study investigated the regulatory role of Pokemon in Sprouty1 expression and the effect on liver cancer cell growth and proliferation, revealing a novel miR‐21‐mediated regulatory circuit. In normal (HL‐7702) and cancer (QGY‐7703) liver cell lines, Sprouty1 expression is inversely correlated with Pokemon levels. Targeted expression or siRNA‐mediated silencing showed that Pokemon is a repressor of Sprouty1 expression at both mRNA and protein levels, but Pokemon cannot affect the promoter activity of Sprouty1. Sprouty1 is a target of miR‐21 and interestingly, we found that miR‐21 is up‐regulated by Pokemon in liver cancer cells. Luciferase reporter assays showed that Pokemon up‐regulated miR‐21 transcription in a dose‐dependent manner, and ChIP assay exhibited a direct binding of Pokemon to the miR‐21 promoter at −747 to −399 bp. Site‐directed mutagenesis of the GC boxes at −684 to −679 bp and −652 to −647 bp of miR‐21 promoter abolished the regulatory activity by Pokemon. Furthermore, we found that the modulation of Pokemon and miR‐21 expression affected the growth and proliferation of liver cancer cells QGY‐7703. In summary, our findings demonstrate that Pokemon suppresses Sprouty1 expression through a miR‐21‐mediated mechanism, affecting the growth and proliferation of liver cancer cells. This study recognized miR‐21 and Sprouty1 as novel targets of the Pokemon regulatory network. J. Cell. Biochem. 114: 1625–1633, 2013. © 2013 Wiley Periodicals, Inc.